Analisis Kesulitan yang Dihadapi Siswa Kelas IV dalam Menyelesaikan Soal Cerita Operasi Hitung Bilangan Cacah di Sekolah Dasar - Unaenah, Een; Setiawan, Rangga Rizky; Pratama, Riski (Lembaga Yasin AlSys, 2023)
Every child should start learning math in elementary school so they can develop the skills necessary to analyze data, perform critical analysis, write creatively, and work together. A student must have these skills to use information. Here, we conduct research as an initial responder to the challenge problems of grade IV students. Utilize descriptive writing methodology. The purpose of this study was to identify hit-and-miss learning problems in public schools. This is a lot. There are several reasons why hitching operations need to be done short and light work, some of which are listed below: 1) Difficulties related to pendular observation Addition 2 Carefully in subtraction protocols using borrowing techniques, 3) Ability to understand literary tropes and ability to apply mathematics. mathematical equations.